Determinants of adherence to diabetes treatment1. (4th March 2015) - Larkin, Amy T.; Hoffman, Christina; Stevens, Adrienne; Douglas, Andrew; Bloomgarden, Zachary
Abstract Background Understanding and improving medication adherence is crucial in diabetes management. Adherence to a diabetes regimen can improve glucose control and limit the development of complications. The aim of the present study was to evaluate the extent to which a variety of factors influence diabetes medication adherence. Methods A medication adherence survey was made available on WebMD, a medical information website for patients and/or consumers. Respondents were residents of the US, ≥18 years old, and diagnosed with either type 1 or type 2 diabetes mellitus (self‐reported). Results Behavioral adherence (self‐reported doses missed per week) correlated with perceived adherence (patients' self‐report of their overall impression of medication adherence, ranked 0–5; P < 0.001). Adherent patients (very few [0%–10%] issues with adherence) were more likely to report having received information from their physician. Mostly adherent patients (few [11%–26%] issues with adherence) were less likely to obtain information from their physician, but reported more medication self‐titration. Somewhat non‐adherent patients (some [27%–46%] adherence issues) reported more "self‐consciousness factors" and hypoglycemia. Non‐adherent patients (many [47%–88%] adherence issues) were more likely to report worries about medication side effects. Conclusions Receiving information from a healthcare provider is associated with greater diabetes medication adherence, suggesting the importance of clinicians making time to provide patient education.